Business Plan Analysis of the Business Feasibility Case Study - Diah Hafni Pardede; Siti Ramadhani Tanjung; Irdinansyah Goli; Amalul'izzi Amalul'izzi; Suhairi Suhairi (Penerbit Jurnal Indonesia, 2022)
This article aims to find out how to standardize a good business plan on business feasibility. A business feasibility study is needed to see a picture of whether or not a business is appropriate to be run, and whether it can grow rapidly or not. For this reason, the author wants to analyze plain business against a business feasibility case study, in this case the author uses a feasibility analysis through several aspects, namely, aspects of planning, implementation and business market share, using descriptive research methods. The data collection method used swot analysis and collected some findings from the literature. So some results obtained from business plan analysis research on business feasibility case studies are that if a business wants to be said to be feasible in its business plan, an owner must carefully think about how the business strategy from several aspects so that the business plan that will be carried out can be said to be feasible.